2019
DOI: 10.1371/journal.pone.0216858
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of virtual reality to reduce chronic low back pain: Proof-of-concept of a non-pharmacological approach on pain, quality of life, neuropsychological and functional outcome

Abstract: Objectives Chronic pain, such as low-back pain, can be a highly disabling condition degrading people’s quality of life (QoL). Not every patient responds to pharmacological therapies, thus alternative treatments have to be developed. The chronicity of pain can lead to a somatic dysperception, meaning a mismatch between patients’ own body perception and its actual physical state. Since clinical evaluation of pain relies on patients’ subjective reports, a body image disruption can be associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 68 publications
2
74
0
6
Order By: Relevance
“…The effect of treadmill training with VR on improving body stability in children with spastic cerebral palsy has been demonstrated [ 59 ]. The effectiveness of VR training focused on body balance has been demonstrated in functional improvement in patients after strokes [ 60 , 61 ], with back pain [ 62 ], as well as in gait re-education and improvement of body balance in patients after TKA [ 63 ]. Blasco et al [ 41 ] researched the efficacy of VR tools for total knee replacement and suggested that an augmented Virtual Reality Tools (VRT) physical therapy could be more effective for overcoming balance limitations than standard physical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of treadmill training with VR on improving body stability in children with spastic cerebral palsy has been demonstrated [ 59 ]. The effectiveness of VR training focused on body balance has been demonstrated in functional improvement in patients after strokes [ 60 , 61 ], with back pain [ 62 ], as well as in gait re-education and improvement of body balance in patients after TKA [ 63 ]. Blasco et al [ 41 ] researched the efficacy of VR tools for total knee replacement and suggested that an augmented Virtual Reality Tools (VRT) physical therapy could be more effective for overcoming balance limitations than standard physical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is a lack of research not only in this respect. In general, less research has been done in the field of augmented reality in connection with pain therapy compared to VR [16,38]. Besides, AR systems and their applications are more cost-intensive compared to VR.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is a lack of research not only in this respect. In general, less research has been done in the eld of augmented reality in connection with pain therapy compared to VR [16,38]. Besides, AR systems and their applications are more cost-intensive compared to VR.…”
Section: Discussionmentioning
confidence: 99%